RISIKO ERGONOMI PENYAKIT AKIBAT KERJA PADA PERAWAT GIGI - Luh Putu Suarniti (Jurnal Kesehatan Gigi (Dental Health Journal), 2015)
Dental nurse’s activity has risk in doing their job. The risk of the disease can be a danger to health (health hazard) or a danger to safety (safety hazard). Prevention of risks must be made by all parties by means of adjustment between workers, work processes and working environment with an approach called ergonomics. Occupational diseases that often occur dental nurses are generally derived from physiological factors. Diseases that often arise are: Musculoskeletal Disorders (MSDs), lower back pain, hernia nucleus pulposus ( HNP ) , and Carpal Turner Syndrome . Prevention is usually done by a nurse to avoid these diseases is to adopt a healthy lifestyle, exercising regularly, and do some engineering or changes in the work environment.